2011
DOI: 10.1007/s11259-011-9491-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a Streptomyces sp. isolate exhibiting activity against multidrug-resistant coagulase-negative Staphylococci

Abstract: The resistance of 220 coagulase-negative Staphylococci (CNS) (associated with animal disease) to 13 antibiotics were determined using the disk diffusion method. 35.9% of multidrug-resistant coagulase-negative Staphylococci (MR-CNS) exhibited resistance to five or more than five antibiotics; all of these bacteria were resistant to methicillin too. The new Streptomyces sp. ABRIINW111 was isolated from the Zagros Mountains Hamadan, Iran. The 16S rDNA sequence of the isolate indicated that it has 98% similarity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
(35 reference statements)
0
18
1
Order By: Relevance
“…This suggests promising antimicrobial potential of extract from ZoA1 (Table 4). Sadigh-Eteghad et al (Sadigh-Eteghad et al 2011) have previously reported the diethyl ether extract of endophytic Streptomyces levis to have antimicrobial effect due to formation of 15 mm zone of inhibition against test organism and the value was less than the results of the present study. Recent reports on broad spectrum antibacterial activity of Nocardiopsis synnemataformans endophytic to Tulsi leaves (21 mm) is supportive to the results obtained in the current study (Singh and Padmavathy 2015).…”
Section: Antibacterial Effects Of Extract From Nocardiopsis Sp Againcontrasting
confidence: 85%
“…This suggests promising antimicrobial potential of extract from ZoA1 (Table 4). Sadigh-Eteghad et al (Sadigh-Eteghad et al 2011) have previously reported the diethyl ether extract of endophytic Streptomyces levis to have antimicrobial effect due to formation of 15 mm zone of inhibition against test organism and the value was less than the results of the present study. Recent reports on broad spectrum antibacterial activity of Nocardiopsis synnemataformans endophytic to Tulsi leaves (21 mm) is supportive to the results obtained in the current study (Singh and Padmavathy 2015).…”
Section: Antibacterial Effects Of Extract From Nocardiopsis Sp Againcontrasting
confidence: 85%
“…Resistance of staphylococcal isolates to methicillin was tested by disk diffusion assay according to the guidelines of the National Committee for Clinical Laboratory Standards (NCCLS, 2003) using Mueller Hinton agar [11]. …”
Section: Methodsmentioning
confidence: 99%
“…The detection of SEs is known as a reliable means for the confirmation of staphylococcal outbreaks and determination of the enterotoxigenicity of strains [9]. On the other hand, due to the intensive use of antibiotics in public health and animal breeding, antibiotic resistance in pathogens including the genus Staphylococcus has become an increasing medical problem during the last decades [10, 11]. Moreover, the methicillin resistant S. aureus (MRSA) should be also considered resistant to all penicillins, cephalosporins, cephems, and other β -lactams [12].…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, the turbidity 620 nm, 0.08 O.D. was considered suitable for inoculation [13]. The assesment of isolated cells purity using flow cytometry…”
Section: Preparation Of Bacterial Samplementioning
confidence: 99%
“…Antibiotics such as Erythromycin, Streptomycin, Tetracycline and a variety of essential extensively-used drugs can be isolated from the Streptomyces species [13]. Secondary metabolites are organic compounds that are not directly associated with the normal growth, development or propagation of a microorganism, unlike primary metabolites that are essential for the growth of microorganisms.…”
Section: Introductionmentioning
confidence: 99%